Progression of hepatic encephalopathy induced by bile duct ligation versus thioacetamide in rats: Regulatory role of apigenin - Ahmed M. Fayez, Dina F. Mansour, Dalia O. Saleh (Journal of Applied Pharmaceutical Science, 2021)
Hepatic encephalopathy (HE) is the decline in brain functions due to liver insufficiency. A high mortality rate was reported due to the rapid progression of HE from covert to overt, leading to detrimental consequences. This study aims to assess the progression of HE and the potential hepatoprotective and neuroprotective effect of apigenin (APG) in bile duct ligation (BDL) versus thioacetamide (TAA)-induced HE models in rats. Wistar albino rats were divided into eight groups; four groups for the BDL model and the other four groups for the TAA model (100 mg/kg, i.p., thrice weekly for five consecutive weeks). APG (20 mg/kg/day) or lactulose (LAC) (8 ml/kg/day), as the standard, was administered orally for three consecutive weeks starting from day 14 of the experiment. Liver enzymes, total bilirubin, serum ammonia, brain and liver glutathione and malondialdehyde, brain dopamine, hepatic interleukin-6, and nuclear factor kappa B were assessed, as well as the beam walking test and histopathological examinations were carried out. APG showed significant anti-hyperammonemic, anti-oxidant, and anti-inflammatory effects in HE groups. Additionally, improvement in behavioral test and histological image of livers and brains of HE rats treated with APG was observed. In conclusion, APG exerted a significant regulatory role compared to LAC in progression of HE in BDL and TAA models.
Keywords: Hepatic encephalopathy, bile duct ligation, thioacetamide, apigenin, rats